Sibiriline, a new small chemical inhibitor of receptor‐interacting protein kinase 1, prevents immune‐dependent hepatitis. (11th August 2017) - Le Cann, Fabienne; Delehouzé, Claire; Leverrier‐Penna, Sabrina; Filliol, Aveline; Comte, Arnaud; Delalande, Olivier; Desban, Nathalie; Baratte, Blandine; Gallais, Isabelle; Piquet‐Pellorce, Claire; Faurez, Florence; Bonnet, Marion; et al.
Abstract : Necroptosis is a regulated form of cell death involved in several disease models including in particular liver diseases. Receptor‐interacting protein kinases, RIPK1 and RIPK3, are the main serine/threonine kinases driving this cell death pathway. We screened a noncommercial, kinase‐focused chemical library which allowed us to identify Sibiriline as a new inhibitor of necroptosis induced by tumor necrosis factor (TNF) in Fas‐associated protein with death domain (FADD)‐deficient Jurkat cells. Moreover, Sib inhibits necroptotic cell death induced by various death ligands in human or mouse cells while not protecting from caspase‐dependent apoptosis. By using competition binding assay and recombinant kinase assays, we demonstrated that Sib is a rather specific competitive RIPK1 inhibitor. Molecular docking analysis shows that Sib is trapped closed to human RIPK1 adenosine triphosphate‐binding site in a relatively hydrophobic pocket locking RIPK1 in an inactive conformation. In agreement with its RIPK1 inhibitory property, Sib inhibits both TNF‐induced RIPK1‐dependent necroptosis and RIPK1‐dependent apoptosis. Finally, Sib protects mice from concanavalin A‐induced hepatitis. These results reveal the small‐molecule Sib as a new RIPK1 inhibitor potentially of interest for the treatment of immune‐dependent hepatitis. Abstract : The receptor‐interacting protein kinase 1 (RIPK1) is a serine/threonine kinase involved in necroptosis. We screened a noncommercial, kinase‐focused compound collection and identified Sibiriline (Sib) as a new potent RIPK1 inhibitor active against immune‐dependent hepatitis. Molecular docking analysis showed that Sib interacts with key amino acids of RIPK1, also involved in the interaction with necrostatin‐1, locking RIPK1 in an inactive conformation.